2011
DOI: 10.1021/cs200336r
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Controlling Reactivity of Unsaturated Oxygenates and Polyols on Metal Catalysts

Abstract: The production of fuels and chemicals from biomass requires heterogeneous catalysts that facilitate selective reactions of highly functional oxygenates. Although designing catalysts for high selectivity is a universal challenge in heterogeneous catalysis research, the problem is particularly acute for highly functional molecules, which contain two or more functional groups that may react over metal surfaces. This perspective article focuses on recent efforts to develop structure–property relations on metal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 180 publications
3
103
0
Order By: Relevance
“…However, when acetol was used as the starting reactant, it was converted completely to 1,2-PDO within 20 min at same reaction conditions. So we deduced that the hydrogenolysis of glycerol in the present catalysis system follows the Langmuir-HinshelwoodHougen-Watson (LHHW) mechanism [33][34][35] in which the adjacent two hydroxyls of glycerol adsorbed on the NiO surface, react with atomic hydrogen on the Ni surface, and the C-O bond cleavage and hydrogen atom addition occur simultaneously to produce 1,2-PDO, as shown in Scheme 1. For the formation of EG, glycerol first of all dehydrogenates to glyceraldehydes, then decarbonylates through retro-aldolization to produce EG [16].…”
Section: Influence Of Ni Metal State On the Catalytic Performancementioning
confidence: 95%
“…However, when acetol was used as the starting reactant, it was converted completely to 1,2-PDO within 20 min at same reaction conditions. So we deduced that the hydrogenolysis of glycerol in the present catalysis system follows the Langmuir-HinshelwoodHougen-Watson (LHHW) mechanism [33][34][35] in which the adjacent two hydroxyls of glycerol adsorbed on the NiO surface, react with atomic hydrogen on the Ni surface, and the C-O bond cleavage and hydrogen atom addition occur simultaneously to produce 1,2-PDO, as shown in Scheme 1. For the formation of EG, glycerol first of all dehydrogenates to glyceraldehydes, then decarbonylates through retro-aldolization to produce EG [16].…”
Section: Influence Of Ni Metal State On the Catalytic Performancementioning
confidence: 95%
“…These catalysts showed high activity (78.1-98.0% conversion) and selectivity 21 (93.6%) increasing with Cu loading ( Table 2, runs 2-4). The results suggest that tartrate 22 ligands play important role in the assembly of metal-organic framework and the formation of 23 sufficient catalytic sites [32,33]. In this procedure operating in alkaline medium the tartrate 24 ligands form complexes with copper (II) that are stable enough to prevent precipitation of 25 copper (II) hydroxide.…”
Section: Introduction 11mentioning
confidence: 99%
“…6 Furthermore, arabinose, galactose, mannose, rhamnose, and maltose 7,8 in addition to glucose 9,10 can be hydrogenated to the corresponding sugar-alcohols on Ru/C catalysts while rhenium can be employed in mono and bi-metallic catalysts for hydrodeoxygenation of several polyols and dehydration of short chain alcohols. [11][12][13] Despite their high relevance as promising biomass-based processes, modeling of these systems is, from the computational point of view, a challenging task mainly related to the definition of a protocol able to describe with reasonable accuracy the interactions between adsorbates and metallic surfaces, in particular within a periodic DFT formalism. Various studies in the recent literature showed that the bonds occurring between OH moieties as well as H 2 O molecules with metals contain non-negligible components originating from the van der Waals (vdW) forces; [14][15][16] therefore, a suitable description of these interactions should be included in order to obtain an accurate modeling of the adsorption process.…”
Section: Introductionmentioning
confidence: 99%